Pengaruh Promosi, Lokasi, dan Harga terhadap Keputusan Pembelian Rumah Subsidi di PT Arza Putra Wahid Persada - Lili Dewi Sabrina; Anzu Elvia Zahara (Lembaga Yasin AlSys, 2025)
The decision to purchase subsidized housing in Indonesia, particularly at PT. Arza Putra Wahid Persada in the Jambi region, is influenced by various external factors such as promotion, location, and price. This study aims to examine the extent to which these three variables affect consumer decisions in selecting subsidized homes. A quantitative approach with a descriptive-verificative design was used. The sample consisted of 97 respondents selected through purposive sampling, targeting lower-middle-income individuals who had accessed information or conducted transactions with the developer. Data collection techniques included Likert-scale questionnaires, semi-structured interviews, observation, and literature review. The data were analyzed using validity and reliability tests, multiple linear regression, partial t-tests, and the coefficient of determination with SPSS version 25. The results show that promotion, location, and price have a positive and significant influence, both simultaneously and partially on purchasing decisions. Promotion shapes perceived value and stimulates buying interest; location is crucial in terms of comfort, accessibility, and proximity to public facilities; while price remains a primary consideration related to purchasing power and perceptions of housing quality. The study concludes that the synergy between promotion, location, and price forms a key strategy in influencing consumer decisions in the subsidized housing segment. These findings provide a valuable foundation for developers and policymakers in designing more targeted marketing approaches. Future research is recommended to explore additional variables and apply mixed or longitudinal methods to gain a more comprehensive understanding.